Study of Gd-doped Bi2Te3 thin films: Molecular beam epitaxy growth and magnetic properties - Harrison, SE; Collins-McIntyre, L; Li, S; Baker, A; Shelford, L; Huo, Y; Pushp, A; Parkin, S; Harris, J; Arenholz, E; van der Laan, G; Hesjedal, T (2014)
Incorporation of magnetic dopants into topological insulators to break time-reversal symmetry is a prerequisite for observing the quantum anomalous Hall (QAHE) effect and other novel magnetoelectric phenomena. GdBiTe3 with a Gd:Bi ratio of 1:1 is a proposed QAHE system, however, the reported solubility limit for Gd doping into Bi2Te3 bulk crystals is between ∼0.01 and 0.05. We present a magnetic study of molecular beam epitaxy grown (GdxBi1-x)2Te 3 thin films with a high Gd concentration, up to x ≈ 0.3. Magnetometry reveals that the films are paramagnetic down to 1.5 K. X-ray magnetic circular dichroism at the Gd M4,5 edge at 1.5 K reveals a saturation field of ∼6 T, and a slow decay of the magnetic moment with temperature up to 200 K. The Gd3 ions, which are substitutional on Bi sites in the Bi2Te3 lattice, exhibit a large atomic moment of ∼7 μB, as determined by bulk-sensitive superconducting quantum interference device magnetometry. Surface oxidation and the formation of Gd2O3 lead to a reduced moment of ∼4 μB as determined by surface-sensitive x-ray magnetic circular dichroism. Their large atomic moment makes these films suitable for incorporation into heterostructures, where interface polarization effects can lead to the formation of magnetic order within the topological insulators. © 2014 AIP Publishing LLC.